Analisis Minat Penggunaan QRIS pada Generasi Milenial Menggunakan Pendekatan TAM di Jawa Timur - Dita Riyanto Putro; Eko Siswanto; Mochammad Danara Indra Pradigta; Bella Amiria Rahmahima (REVITALISASI : Jurnal Ilmu Manajemen, 2023)
This study aims to analyze -- (Qris) with the Technology Acceptance Model (TAM) approach which is expanded by adding subjective norms and perceptions of security as exogenous variables. Subjective norms are hypothesized to influence intention to use, either directly or indirectly through endogenous variables in TAM. Meanwhile, the perceived security variable is hypothesized to have a direct effect. Overall the proposed hypothesis forms a research framework in the structural equation model (SEM). Empirical data was obtained through an online survey of 233 respondents who answered 23 complete questionnaire questions. The selection of respondents was determined using a purposive-non-probability sampling approach from active users of the Quick Response Indonesia Standard (Qris) at various banks in East Java whose population size is unknown. The software used to inform that all the indicators used meet the validity and reliability criteria, the research model meets the suitability criteria. The five TAM variables and their extensions have a positive and acceptable effect on intention to use. The biggest influence of the antecedent variables on the intention to use successively is subjective norm, perceived usefulness, attitude, perceived ease of use, and the smallest is perceived security.